(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
In this article is reported about fungal species contaminating spices: red pepper, black pepper, suneli, carry. Data about 29 species of fungi contaminating spices are given. Isolated species belong to Zygomycetes and Deuteromycetes classes. 21 species belong to Moniliaceae family.